Impact of body mass index on early and mid-term outcomes after surgery for acute Stanford type A aortic dissection - Yanxiang Liu; Bowen Zhang; Shenghua Liang; Yaojun Dun; Luchen Wang; Haoyu Gao; Jie Ren; Hongwei Guo; Xiaogang Sun (Journal of Cardiothoracic Surgery, 2021)
Abstract Background Obesity is dramatically increasing worldwide, and more obese patients may develop aortic dissection and present for surgical repair. The study aims to analyse the impact of body mass index (BMI) on surgical outcomes in patients with acute Stanford type A aortic dissection (ATAAD). Methods From January 2017 to June 2019, the clinical data of 268 ATAAD patients in a single centre were retrospectively reviewed. They were divided into three groups based on the BMI: normal weight (BMI 18.5 to < 25 kg/m2, n = 110), overweight (BMI 25 to < 30 kg/m2, n = 114) and obese (BMI ≥30 kg/m2, n = 44). Results There was no statistical difference among the three groups in terms of the composite adverse events including 30-day mortality, stroke, paraplegia, renal failure, hepatic failure, reintubation or tracheotomy and low cardiac output syndrome (20.9% vs 21.9% vs 18.2% for normal, overweight and obese, respectively; P = 0.882). No significant difference was found in the mid-term survival among the three groups. The proportion of prolonged ventilation was highest in the obese group followed by the overweight and normal groups (59.1% vs 45.6% vs 34.5%, respectively; P = 0.017). Multivariable logistic regression analysis suggested that BMI was not associated with the composite adverse events, while BMI ≥30 kg/m2 was an independent risk factor for prolonged ventilation (OR 2.261; 95% CI 1.056–4.838; P = 0.036). Conclusions BMI had no effect on the early major adverse outcomes and mid-term survival after surgery for ATAAD. Satisfactory surgical outcomes can be obtained in patients with ATAAD at all weights.